Direct Toll‐Like Receptor 8 signaling increases the functional avidity of human CD8+ T lymphocytes generated for adoptive T cell therapy strategies. Issue 1 (19th February 2015) - Chatillon, Jean‐François; Hamieh, Mohamad; Bayeux, Florence; Abasq, Claire; Fauquembergue, Emilie; Drouet, Aurélie; Guisier, Florian; Latouche, Jean‐Baptiste; Musette, Philippe
Abstract: Adoptive transfer of in vitro activated and expanded antigen‐specific cytotoxic T lymphocytes (CTLs) is a promising therapeutic strategy for infectious diseases and cancers. Obtaining in vitro a sufficient amount of highly specific cytotoxic cells and capable of retaining cytotoxic activity in vivo remains problematic. We studied the role of Toll‐Like Receptor‐8 (TLR8) engagement on peripheral CTLs activated with melanoma antigen MART‐1‐expressing artificial antigen‐presenting cells (AAPCs). After a 3‐week co‐culture, 3–27% of specific CTLs were consistently obtained. CTLs expressed TLR8 in the intracellular compartment and at the cell surface. Specific CTLs activated with a TLR8 agonist (CL075) 24 h before the end of the culture displayed neither any change in their production levels of molecules involved in cytotoxicity (IFN‐γ, Granzyme B, and TNF‐α) nor major significant change in their cell surface phenotype. However, these TLR8‐stimulated lymphocytes displayed increased cytotoxic activity against specific peptide‐pulsed target cells related to an increase in specific anti‐melanoma CTL functional avidity. TLR8 engagement on CTLs could, therefore, be useful in different immunotherapy strategies. Abstract : In our study, TLR8 engagement on cytotoxic T lymphocytes has led to a higher cytotoxic capacity and functional avidity on these cells. To our knowledge, this is the first report of a direct effect of TLR8 engagement on human cytotoxic CD8+ T cells.